Complications pertaining to the detection and characterization of individual and embedded single walled carbon nanotubes by scanning electron microscopy - Alvin Orbaek White (Nanoscale, 2013)
Comparison of AFM and SEM images of single walled carbon nanotubes (SWNTs) grown within a dielectric matrix reveal subterranean nanotubes that are present within the matrix, and as such can be charge screened by the dielectric. Under adequate imaging conditions for the SWNT/silica sample the intensity of isolated nanotubes is found to be inversely proportional to the instrument dwell time (i.e., shorter dwell times were found to make SWNT intensities brighter). The threshold dwell time required to enable isolated tubes to be visible was found to be 10 μs; moreover, the degree change in intensity was found to be nanotube specific, i.e., different SWNTs respond in a different manner at different dwell times. The results indicate that care should be taken when attempting to quantify number density and length distributions of SWNTs on or within a dielectric matrix.